MANAJEMEN SUMBER DAYA MANUSIA PONDOK PESANTREN SHUFFAH HIZBULLAH NATAR LAMPUNG SELATAN - Ahmad Fauzan Fauzan (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
Abstract. This research is aimed to describe human resource management in Shuffah Hisbullah Natar, South Lampung. This research uses qualitative approach. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction measures, data display and conclucion. From the results of this study, 1) Analysis and design of the work has been done, 2) Recruitment process at Shuffah Hizbullah Pondok Pesantren started when the boarding school felt new additional needs, 3) Selection is done on prospective employees by looking at their competence, 4) Orientation or introduction in the cottage pesantren has been started in the last few years, 5) Human resources training held in boarding school and outside boarding school, 6) Planning and career development in Shuffah Hizbullah Pesantren has not been so planned. Keywords: management, human resources